Influência da velocidade e posição de soldagem nas propriedades de juntas soldadas pelo processo de eletrodo revestido - Silva, Nicholas Michael Caesar Sene e [UNESP] (2017)
Shielded metal arc welding is usually used in the metal-mechanical industry and, controlling microstructure as well as mechanical properties of a welded joint, based on welding parameters, is definitively important in engineering applications. Therefore, the purpose of this work is to evaluate the influence of both position and welding velocity on the properties of a low carbon steel weld joint, obtained using shielded metal arc welding. Four welded joints were obtained, two of them in the flat position and two in the vertical up position; two different welding velocities were used for each position. Conventional metalographic analysis was performed in order to compare the obtained microstructures for each welded joint as well as the micro Vickers hardness profile was determined in order to evaluate the influence of the welding parameters under study. It was observed that microstructures behave just like expected while the hardness profiles revealed the opposite response to that expected, which was attributed to different number of beads in each sample